2022
DOI: 10.1371/journal.pone.0277180
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary magnesium intake and glycohemoglobin with mortality risk in diabetic patients

Abstract: Background Dietary magnesium intake inversely correlated to risk of death in general population. However, it is relatively unknown whether the beneficial effect remains significant in individuals with diabetes. Our study purpose is to evaluate the association of dietary magnesium intake with mortality risk in diabetic population. Methods The study population is recruited from 2003–2014 National Health and Nutrition Examination Survey, totaling 2,045 adults with diabetes being included. Participants were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Not only does lower magnesium intake per day increase the prevalence of diabetes mellitus, but it has also been linked to a higher mortality in these patients. Wang et al [ 40 ] found in a retrospective analysis on 2045 diabetic subjects (average age of 52.9 ± 10.1 years, a mean body mass index of 33.6 ± 8 kg/sqm) that an intake of less than 250 mg/day increased the risk both of all-cause mortality and of mortality of other causes excluding cardiovascular and neoplasia [ 40 ]. This connection was also shown in a prospective study on 4699 diabetic individuals whereas higher dietary magnesium intake was associated with lower all-cause mortality [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only does lower magnesium intake per day increase the prevalence of diabetes mellitus, but it has also been linked to a higher mortality in these patients. Wang et al [ 40 ] found in a retrospective analysis on 2045 diabetic subjects (average age of 52.9 ± 10.1 years, a mean body mass index of 33.6 ± 8 kg/sqm) that an intake of less than 250 mg/day increased the risk both of all-cause mortality and of mortality of other causes excluding cardiovascular and neoplasia [ 40 ]. This connection was also shown in a prospective study on 4699 diabetic individuals whereas higher dietary magnesium intake was associated with lower all-cause mortality [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…To conclude, we identified three studies related to the daily dietary determinant and diabetic complications (n = 3 studies of different designs, namely, one cross-sectional, one prospective, and another case–control study) in terms of retinopathy (n = 1, N = 3794) and nephropathy (n = 2, N = 4805) that suggested a lower intake was associated with a higher risk of such complications. Additionally, two other studies (one prospective and one retrospective cohort) focused on mortality (N = 6744), which, taking only certain mortality indicators into consideration, might be decreased in the subgroups with a higher micronutrient intake ( Table 4 ) [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…We recalculated the results of meta-analyses that used a fixed effect model, or did not provide I² values or forest plots, to ensure valid meta-estimates with 95% confidence intervals to provide an evaluation of the certainty of evidence based on the GRADEpro The main limitation of our umbrella review was that recently published randomised controlled trials not yet included in systematic reviews and metaanalyses were not considered in our report. [56][57][58] Also, we did not explore subgroup analyses (eg, by sex, race, or duration of diabetes) or sensitivity analyses (eg, excluding studies with a high risk of bias). We used the DerSimonian and Laird approach 28 for recalculation of extracted estimates with the random effects meta-analyses, but the Hartung and Knapp method might perform better in terms of more adequate error rates, especially when the number of studies was small.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Участь магнію у клітинних процесах. Припускають, що магній відіграє ключову роль в метаболізмі вуглеводів, що може пояснювати його роль при цукровому діабеті 2 типу [6]. Також він має важливе значення для реплікації і підтримки стабільності ДНК, а також приймає участь в транскрипції РНК.…”
Section: Theoretical and Experimental Medicineunclassified